The Effect of Smog-Ozone Warnings and a Vanpool Program on Traffic Volume in York County of South Carolina. (April 2015) - Giovanis, Eleftherios
Ground-level ozone is a critical criteria pollutant that is significantly generated by transportation patterns. We study the effect of smog-ozone warnings, triggered by the Environmental Protection Agency, on traffic volume in York County, South Carolina during the period 2006–10. In addition, the subperiods 2006–07 and 2008–10, where the ozone smog-alert thresholds 0.080 parts per million (ppm) and 0.075 ppm, respectively, are examined. The approach followed in this paper is a differences-in-differences (DID) regression. Additionally, a regression discontinuity design in the DID framework is applied. We find a negative and significant decrease in weekday peak-hour traffic volume in the treatment group during 2008–10.